Data Mining in Career Counselling for Efficient and Effective Education System (EDM) - Singla, Anshu; Garg, Sachin (International Journal of Computer Sciences and Engineering, 2018)
This is a review paper on using Data mining techniques for students in their career path and their prediction of performance .Many Techniques of data mining like Classification, Clustering, and Association Rules are used for Educational Data Mining System. Educational Data Mining is knowledge extraction from many datasets, databases and data repository in different perspective. This Paper studies many papers which surveys data mining applications and techniques that can help students for their career counseling. Weka is the powerful tool used for Data Mining Techniques. Weka J48 tool is used for decision tree classifier .Supervised Learning is used here for improving efficiency of EDM. The algorithms like classification, clustering, outlier detection, association rule, prediction etc which are used in Educational Data Mining Systems Data Mining Techniques are also here used for improving the Education System Efficiency .There is need for right counseling of student such that proper productivity of Human Resource Can be Utilized.